History of investigation and current classification of coronaviruses (Nidovirales: Coronaviridae) - M. Yu. Shchelkanov (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
An epidemic of COVID-19 (Coronavirus disease 2019) etiologically associated with the SARS-CoV-2 (Severe acute respiratory syndrome-related coronavirus 2) that occurred at the turn of 2019–2020 firstly in Wuhan (Hubei province of China) and then spread to many countries around the world rose a new wave of interest to coronaviruses. The first coronaviruses – members of the Coronaviridae family belonging to the order Nidovirales — were discovered in the first half of the last century. The first human coronavirus, HCoV-B814, was isolated in 1965 that was not preserved in available virological collections. Over the last time, old-fashioned names and terms have been overlapped. By the beginning of the XXI century coronaviruses posed a serious veterinary problem but it was believed that epidemic coronaviruses were not among highly dangerous viruses. Scientific community had to revise such views first in 2002 when SARS-CoV (Severe acute respiratory syndrome-related coronavirus) was transferred to human population in the Southeast Asia from bats, and then in 2012 when natural foci of the MERS-CoV (Middle East respiratory syndrome-related coronavirus) were found on the territory of the Arabian Peninsula. Due to an increased interest in coronaviruses, a large number of new Coronaviridae members was discovered in the first two decades of the XXI century, which required to revise its taxonomic structure several times. This review is aimed at outlining a history of investigating coronaviruses and their current classification that was shaped in early 2020 in accordance to the last recommendations of the International Committee on Taxonomy of Viruses.